Algebras of binary formulas for weakly circularly minimal theories with equivalence relations - Kulpeshov, B.Sh. (Eurasian Mathematical Journal, 2025)
Algebras of binary isolating formulas are described for \(_0\)-categorical 1-transitive non-primitive weakly circularly minimal theories of convexity rank greater than 1 with a trivial definable closure, having only equivalence relations.